Regulation of secretion in Clara cells: studies using the isolated perfused rat lung. - Massaro, G D (1981)
Previous studies from our laboratory indicated that both beta-adrenergic and cholinergic agents stimulate in vivo secretion by rat bronchiolar Clara cells. Those studies also provided support for an in-series beta-adrenergic-cholinergic stimulation of secretion. To further explore the regulation of secretion in Clara cells, and to do it in the absence of systemic influences, we have used the isolated ventilated perfused rat lung. We have again used morphometry and electron microscopy to assess secretion by measuring the volume density (fraction of cell volume) of the secretory granules of bronchiolar Clara cells. We found that in the isolated perfused lung, as in the intact animal, isoproterenol stimulated secretion in Clara cells and that this effect was blocked by the beta-adrenergic antagonist propranolol. Pilocarpine, unlike its action in the intact animal, did not stimulate secretion in the isolated lung; rather it inhibited the secretory effect of isoproterenol. Increased tidal-volume ventilation stimulated secretion; propranolol did not block this effect. Analogs of cyclic (c)AMP and of cGMP also stimulated secretion by Clara cells. These findings indicate that there are at least two mechanisms by which Clara cells can be stimulated to secrete. One seems to be beta-adrenergic-cAMP mediated but the triggering event is unknown. The other is initiated by increased tidal volume and cGMP may be involved in the intracellular mediation of this stimulatory event. Finally, we found evidence of beta-adrenergic (stimulatory) -cholinergic (inhibitory antagonism in the regulation of secretion in Clara cells.